1998
DOI: 10.1038/bjc.1998.712
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinase (MMP-2 and -9) expression in gastrointestinal malignancy

Abstract: Summary The aim of the study was to investigate expression of the active and inactive gelatinases (MMP-2 and -9) in colorectal neoplasia and gastric cancer compared with normal mucosa. A total of 53 colorectal cancers and corresponding normal mucosa were studied using gelatin zymography as well as 15 colorectal adenomas and 13 gastric cancers with corresponding normal mucosa. Overexpression of all the gelatinases occurs in both colorectal and gastric cancer, with activation of MMP-2 appearing to be a feature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
79
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 35 publications
(38 reference statements)
15
79
0
3
Order By: Relevance
“…Thus there is not only more MMP-2 present in tumour than in normal tissue, but the ratio active to proenzyme also increases substantially. A similar finding was reported by Parsons et al (1998) and McKerrow et al (2000) and supports the view that the activation of MMP-2 is a crucial step in tumour invasion. Expression of MMP-2 mRNA in tumour has been described in stromal fibroblastic cells (Poulsom et al, 1992;Newell et al, 1994), but MMP-2 protein appears to be localised predominantly in the cytoplasm of tumour cells (Ring et al, 1997).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 91%
See 3 more Smart Citations
“…Thus there is not only more MMP-2 present in tumour than in normal tissue, but the ratio active to proenzyme also increases substantially. A similar finding was reported by Parsons et al (1998) and McKerrow et al (2000) and supports the view that the activation of MMP-2 is a crucial step in tumour invasion. Expression of MMP-2 mRNA in tumour has been described in stromal fibroblastic cells (Poulsom et al, 1992;Newell et al, 1994), but MMP-2 protein appears to be localised predominantly in the cytoplasm of tumour cells (Ring et al, 1997).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 91%
“…This finding is new since previous studies reported difficulty in measuring the active form, because of its unstability (Parsons et al, 1998) or presumed low levels (Liabakk et al, 1996). In CRC it has been shown that MMP-9 mRNA is expressed in macrophages especially in the invasive site.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 63%
See 2 more Smart Citations
“…The gelatinases, MMP-2 and MMP-9, have been particularly implicated in tumour invasion and metastasis formation (Poulsom et al, 1992;Parsons et al, 1998;Zeng et al, 1999). The primary substrate for these enzymes is type IV collagen, a major component of the basement membrane, which represents a substantial barrier for tumour cell metastasis.…”
mentioning
confidence: 99%